Casualty between advertising and consumption in India - Philip, Abey (Institute of Public Enterprise, 2009)
This study makes use of co-integration methodology to validate the evidence of soundness of advertising and consumption pattern of India during the period of 1980-2006. Augmented Dickey-Fuller test, Philips- Peron Test, Cointegration technique and Error Correction Models have been employed to relate between advertising and consumption. The analysis reveals categorically that there is strong bi-directional relationship between advertising and consumption pattern in India. The consumption pattern in Indian economy is strongly influenced by advertising.